ACTUALIZATION OF VALUES IN PRE-SCHOOL EDUCATION BY IMPLEMENTING COMPETENCE-BASED LEARNING CONTENT - Delijeva, Gunita; Ozola, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Since 2018, competence-based learning content is being introduced in educational institutions of Latvia focusing on interdependent development of knowledge, skills, attitudes and values. If values are actualized in the educational process, the child gradually develops understanding of values from an early age. Thus, value-oriented pre-school education creates preconditions for the continuous development of a responsible and tolerant society and contributes to the common values that determine its direction.The aim of the study is to explore, based on the normative regulation of values in education, the actualization of values in the context of the implementation of competence-based learning content in educational institutions implementing pre-school education curricula. The study is based on the data analysis of the monitoring survey of the Ministry of Education and Science of the Republic of Latvia on the implementation of competence-based learning content during the 2019-2020 school year. The study combines quantitative and qualitative research methods. Data were analyzed using descriptive and inferential statistics as well as qualitative content analysis.The analysis of the survey data shows that in the educational institutions that implement pre-school education curricula, all values defined in the normative regulation, i.e., life, human dignity, freedom, family, marriage, work, nature, culture, the Latvian language and the State of Latvia, as well as other values set by educational institutions are actualized.